2020
DOI: 10.3389/fphar.2020.572373
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Effects of Salvianolic Acid B Against Oxidative Damage

Abstract: Salvianolic acid B (Sal B) is one of the main active ingredients of Salvia miltiorrhiza, with strong antioxidant effects. Recent findings have shown that Sal B has anti-inflammatory, anti-apoptotic, anti-fibrotic effects and can promote stem cell proliferation and differentiation, and has a beneficial effect on cardiovascular and cerebrovascular diseases, aging, and liver fibrosis. Reactive oxygen species (ROS) include oxygen free radicals and oxygen-containing non-free radicals. ROS can regulate cell prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 148 publications
(177 reference statements)
1
60
0
Order By: Relevance
“…It shows strong antioxidant, anti-inflammatory, antifibrotic, and anti-apoptotic capacities (Cao et al, 2012). It can exert its antioxidant effects by directly scavenging ROS or by increasing the expression of different antioxidant enzymes such as SOD, GPx, and HO-1 or inhibiting the expression of Nox2 and Nox4; being the regulation of the Nrf2 pathway the core target of these antioxidant mechanisms (Xiao et al, 2020) (Figure 2).…”
Section: Salvianolic Acid Bmentioning
confidence: 99%
“…It shows strong antioxidant, anti-inflammatory, antifibrotic, and anti-apoptotic capacities (Cao et al, 2012). It can exert its antioxidant effects by directly scavenging ROS or by increasing the expression of different antioxidant enzymes such as SOD, GPx, and HO-1 or inhibiting the expression of Nox2 and Nox4; being the regulation of the Nrf2 pathway the core target of these antioxidant mechanisms (Xiao et al, 2020) (Figure 2).…”
Section: Salvianolic Acid Bmentioning
confidence: 99%
“…Additionally, salvianolic acid B decreases mice interleukin-1 beta-induced colitis recurrence (Feng et al 2020 ). Ragarding its effects on the skeletal system, salvianolic acid B promotes new bone formation and protects against oxidative damage (Kayalar et al 2020 ; Xiao et al 2020 ; Bian and Xiang 2020 ); it improves atherosclerosis by inhibiting the YAP/TAZ/JNK signaling pathway in endothelial cells and pericytes (Yang et al 2020 ). In the nervous system, salvianolic acid B could improve the cognitive impairment of mice infected with Porphyromonas gingivalis by inhibiting neuroinflammation and reducing Aβ level (Liu et al 2020 ).…”
Section: Trpcs Antagonistsmentioning
confidence: 99%
“…Salvianolic acid B (Sal B) is a major bioactive compound extracted from Salviae miltiorrhiza. It has important effects on various organs such as the heart, brain, liver, kidney and intestines [ 26 ]. It has been shown that Sal B has antioxidant [ 21 , 27 ], anti-inflammatory and anti-fibrotic effects, and inhibits apoptosis [ 28 ].…”
Section: Introductionmentioning
confidence: 99%